Preparation and characterization of biopolymers comprising chitosan-grafted-ENR via acid-induced reaction of ENR50 with chitosan - M. R. H. Mas Haris; G. Raju (eXPRESS Polymer Letters, 2014)
This paper describes the first detailed tailored-approach for the preparation of biopolymers comprising chitosan (CTS) grafted onto the backbone of epoxidized natural rubber (CTS-g-ENR). In a typical experiment, appropriate amount of CTS and AlCl3•6H2O was added to a specified amount of ENR50 (ENR with about 50% epoxy content) dissolved in a dual-solvent consisting of 1,4-dioxane and water (97.5:2.5% v/v) and the resulting mixture refluxed with continuous stirring for 6 hours. Nuclear magnetic resonance (NMR) spectral analysis of a biocomposite, CTS-g-ENR-P1, revealed that its epoxy content is 22.36% which is considerably lower than 44.93% as determined for ENR50-control (ENR50 derivative obtained under similar experimental condition but in the absence of CTS). This means that the grafting of CTS onto the backbone of ENR had occurred. The revelation is affirmed by the presence of the characteristic absorption bands of CTS and ENR, and the appearance of new bands at 1219, 902 and 733 cm–1 in the Fourier transform infrared (FTIR) spectrum of CTS-g-ENR-P1. Further evidence that CTS had been successfully grafted onto the backbone of ENR can be deduced and described in this paper from the data obtained by means of Differential Scanning Calorimetric analysis, Thermogravimetric analysis and Variable Pressure Scanning Electron Microscopy.